Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Realistic Mathematic Education (RME) Menggunakan Rumah Adat Bubungan Lima dalam Meningkatkan Hasil Belajar pada Materi Bangun Ruang Kelas V Sekolah Dasar - Jusni Megawati; Agus Susanta; Abdul Muktadir (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to make RME-based worksheets using the Bubungan Lima traditional house in improving learning outcomes in class V elementary school building material. LKPD is made by combining text, pictures and examples using the Bubungan Lima traditional house. The research was conducted at SDN 27 Bengkulu Tengah in class V. This research was research and development (Reseach and Development) with a 4D model, namely the stages of defining, designing, developing, and disseminating. The research object is the RME-based LKPD in Mathematics subject of geometric shapes (cubes and blocks). The instruments used were a feasibility test questionnaire and a teacher and student response questionnaire. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 linguists and 2 presentation experts. The user response test was carried out on 20 grade V students and 1 class teacher at SDN 27 Bengkulu Tengah. Data analysis was used to determine the validity of LKPD using cross-tabulations and distribution of questionnaires for student responses and interviews for teacher responses in using LKPD. The results of interviews with class V teachers showed a positive response. In other words, the LKPD used provides benefits and is effective for use as supporting teaching materials and is able to improve student learning outcomes.